2013
DOI: 10.2113/gssgfbull.184.1-2.67
|View full text |Cite
|
Sign up to set email alerts
|

Seismic anisotropy beneath the northeastern Caribbean: implications for the subducting North American lithosphere

Abstract: Active plate boundaries in the Caribbean form a complex tectonic environment that includes transform and subduction zones. The Caribbean-North American plate boundary is one such active margin, where subduction transitions from arc- to oblique-type off the northeast coast of Puerto Rico. Understanding mantle flow in this region will not only help determine the nature of tectonic activity and mantle dynamics that control these margins, but will also aid our understanding of the fate of subducting lithosphere. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The North America plate is obliquely subducting beneath the Caribbean plate along the obtuse northern corner of the Lesser Antilles arc, northeast of Puerto Rico and the Virgin Islands. Subduction under an obtuse corner is expected to create geometric complications and as some have suggested, segmentation of the slab [ ten Brink and López‐Venegas , ; ten Brink , ; Dillon et al ., ; McCann and Sykes , ; Meighan and Pulliam , ; Meighan et al ., ]. An actively propagating slab tear is suggested to be the dominant process affecting local tectonics, based on the trench's bathymetry and negative gravity anomaly, stress changes along the trench corner related to seafloor asperities, timing of the trench collapse, seismic anisotropy, continuous Global Positioning System (GPS) vector analyses, and seismic swarm activity [ ten Brink and López‐Venegas , ; ten Brink , ; Meighan and Pulliam , ; Meighan et al ., ].…”
Section: Tear Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The North America plate is obliquely subducting beneath the Caribbean plate along the obtuse northern corner of the Lesser Antilles arc, northeast of Puerto Rico and the Virgin Islands. Subduction under an obtuse corner is expected to create geometric complications and as some have suggested, segmentation of the slab [ ten Brink and López‐Venegas , ; ten Brink , ; Dillon et al ., ; McCann and Sykes , ; Meighan and Pulliam , ; Meighan et al ., ]. An actively propagating slab tear is suggested to be the dominant process affecting local tectonics, based on the trench's bathymetry and negative gravity anomaly, stress changes along the trench corner related to seafloor asperities, timing of the trench collapse, seismic anisotropy, continuous Global Positioning System (GPS) vector analyses, and seismic swarm activity [ ten Brink and López‐Venegas , ; ten Brink , ; Meighan and Pulliam , ; Meighan et al ., ].…”
Section: Tear Regionsmentioning
confidence: 99%
“…Furthermore, seamounts are resistant to subduction [ Gutscher et al ., ] and stress modeling has confirmed that large tensile stresses have developed within the slab, down dip of the seamount [ ten Brink , ; Toda and Stein , ]. Mantle flow patterns inferred from crustal seismic anisotropy studies, generally parallel the Caribbean plate boundaries [ Meighan and Pulliam , ; Piñero‐Feliciangeli and Kendall , ; Russo et al ., ; Russo and Silver , ]. One exception was observed off the NE corner of Puerto Rico where flow (inferred from crustal anisotropy) is trench normal and suggests passage of mantle material through a gap in the slab [ Meighan and Pulliam , ].…”
Section: Tear Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The locations of the North American subduction slab and North Caribbean subducting slab are separated discussions in previous studies (McCann, ; Mendoza and McCann, ; Meighan and Pulliam, ; Meighan et al ., ; ten Brink, ). However, we consider the tectonic activity in this area to be controlled by both subduction zones.…”
Section: Integrated Studies Of Gravity and Tomographic Datamentioning
confidence: 99%
“…ten Brink and Granja Bruña () proposed that bivergent thrusting exists on both sides of the PRVI. In addition, previous research (ten Brink, ; Meighan and Pulliam, ) on the southward subduction of the North American Plate suggested that the North American subduction slab splits in the eastern PRVI. So far, however, no models have been attempted to include the influence of the North Caribbean subducting slab because of few evidences, although the North Caribbean subduction zone and North American subduction zone could both have affected the tectonic evolution of the PRVI.…”
Section: Introductionmentioning
confidence: 99%